Circulating tryptophan-kynurenine pathway metabolites are associated with all-cause mortality among patients with stage I-III colorectal cancer - Damerell, Victoria; Klaassen-Dekker, Niels; Brezina, Stefanie; Ose, Jennifer; Ulvik, Arve; van Roekel, Eline H.; Holowatyj, Andreana N.; Baierl, Andreas; Böhm, Jürgen; Bours, Martijn J. L.; Brenner, Hermann; de Wilt, Johannes H. W.; et al. (International journal of cancer, 2024)
Alterations within the tryptophan-kynurenine metabolic pathway have been linked to the etiology of colorectal cancer (CRC), but the relevance of this pathway for prognostic outcomes in CRC patients needs further elucidation. Therefore, we investigated associations between circulating concentrations of tryptophan-kynurenine pathway metabolites and all-cause mortality among CRC patients. This study utilizes data from 2102 stage I-III CRC patients participating in six prospective cohorts involved in the international FOCUS Consortium. Preoperative circulating concentrations of tryptophan, kynurenine, kynurenic acid (KA), 3-hydroxykynurenine (HK), xanthurenic acid (XA), 3-hydroxyanthranilic acid (HAA), anthranilic acid (AA), picolinic acid (PA), and quinolinic acid (QA) were measured by liquid chromatography-tandem mass spectrometry. Using Cox proportional hazards regression, we examined associations of above-mentioned metabolites with all-cause mortality, adjusted for potential confounders. During a median follow-up of 3.2 years (interquartile range: 2.2-4.9), 290 patients (13.8%) deceased. Higher blood concentrations of tryptophan, XA, and PA were associated with a lower risk of all-cause mortality (per doubling in concentrations: tryptophan: HR = 0.56; 95%CI:0.41,0.76, XA: HR = 0.74; 95%CI:0.64,0.85, PA: HR = 0.76; 95%CI:0.64,0.92), while higher concentrations of HK and QA were associated with an increased risk of death (per doubling in concentrations: HK: HR = 1.80; 95%CI:1.47,2.21, QA: HR = 1.31; 95%CI:1.05,1.63). A higher kynurenine-to-tryptophan ratio, a marker of cell-mediated immune activation, was associated with an increased risk of death (per doubling: HR = 2.07; 95%CI:1.52,2.83). In conclusion, tryptophan-kynurenine pathway metabolites may be prognostic markers of survival in CRC patients.
Gesehen am 23.05.2025